PENGOLAHAN AIR PAYAU MENGGUNAKAN TEKNOLOGI MEMBRAN SISTEM OSMOSA BALIK SEBAGAI ALTERNATIF PEMENUHAN KEBUTUHAN AIR MINUM MASYARAKAT KEPULAUAN SERIBU - Widayat, Wahyu (Center for Environmental Technology, 2005)
Kepulauan seribu (Seribu Archipelago) is one of region of north jakarta, the province of DKI Jakarta Raya which is populated by around 18.000 inhabitants. It consists of 111 small islands. Among them, there are about 11 (eleven) islands are stated as the residential: Ã‚Â Ã‚Â P. Untung Jawa, P. Tidung Besar, P. Lancang Besar, P. Panggang, P. Pramuka, P. Kelapa I, P. Kelapa II, P. Harapan, P. Sebira. P. Payung dan P. Pari. P. Panggang and P. Kelapa I are the most populated.In relation to the clean water supply, specifically for drinking water/freshwater, mostly is got from the narrow well, rainfall and some water treatment installations that heve been owned by some islands. However, problem arises when the prolong dry season comes as the quality of water in the narrow well decreases significantly, the well water became brackish. In order to cope this problem, the avaibility of sufficient water treatment installations to process brackish water into freshwater is very important. The water treatment installation with reverse osmosis system is one of the most effective alternative in order to provide the freshwater for the people in the islands. The system has also been aplied sufficiently in several islands, such as P. Kelapa I, P. Tidung, P. Pramuka, P. Untung Jawa, P. Panggang dan P. HarapanÃ‚Â Kata Kunci : Pengolahan Air payau, Osmosa balik, Air minum.